Planting Ages Inhibited Soil Respiration and CO2-C Emissions Attribute to Soil Degradation in Gravel-Mulched Land in Arid Areas - Bingyao Wang; Yunfei Li; Zhixian Liu; Peiyuan Wang; Zhanjun Wang; Xudong Wu; Yongping Gao; Lichao Liu; Haotian Yang (Land)
Gravel mulching is a widely employed strategy for water conservation in arid agricultural regions, with potential implications for soil carbon (C) sequestration and greenhouse gas emissions. However, soil respiration and CO2-C emissions remain uncertain owing to less consideration of the influence of precipitation patterns and planting age. In this study, we investigated the soil respiration rate (Rsoil) and cumulative CO2-C emission (Ccum), both measured over a period of 72 h, along with soil properties and enzyme activities under different precipitation conditions based on gravel mulching with different planting ages. We analyzed the effects of planting ages on Rsoil and Ccum and revealed the underlying mechanisms driving changes in environmental factors on Rsoil and Ccum. The results demonstrated that the Rsoil reached the maximum value at about 1 h, 0.5 h, and 0.25 h after rewetting in 1, 10, and 20 years of gravel mulching under the condition with 1 mm, 5 mm, and 10 mm of precipitation, respectively, whereas the Rsoil exhibited its maximum at about 8 h after soil rewetting under precipitation of 30 mm. The Ccum induced by precipitation pulses tends to decrease with increasing years of gravel mulching. The Ccum was 0.0061 t ha−1 in the 20-year gravel-mulched soil, representing a 53.79% reduction compared to the 1-year gravel-mulched soil. Soil organic matter (SOM), planting ages, and alkaline phosphatase (ALP) were the primary factors influencing the Rsoil and Ccum in 0–20 cm, while SOM, planting ages, and soil porosity (AirP) were the key factors affecting the Rsoil and Ccum in 20–40 cm. The Rsoil and Ccum in the 0–20 cm soil were regulated by soil enzyme activities, while those of 20–40 cm soil were controlled by soil properties. This indicates that the decrease in Rsoil and Ccum is caused by soil degradation, characterized by a decrease in SOM and ALP. This study offers a novel insight into the long-term environmental impact of gravel mulching measures in arid areas, which is helpful in providing a theoretical basis for dryland agricultural management. It is imperative to consider the duration of gravel mulching when predicting the potential for C sequestration in arid agricultural areas.